PENGARUH KEPEMIMPINAN DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI (Studi pada Badan Penelitian dan Pengembangan Departemen Dalam Negeri) - Sri Murgiyati (Widyariset, 2010)
The aim of this study is to analyze the correlation between the leadership, emotional intelligence, and performance. The focus of analysis is to clarity the perspective that high score of leadership and emotional intelligenceto be a performance. This research used scale instrument of leadership, emotional intelligence, and performance to collect the data. This research was done towards 100 staffs of Badan Litbang Depdagri. In analyzing the data, the researcher used product moment correlation that is provided by SPSS. The result showed that there is a positive correlation between leadership, emotional intelligence, and performance at office.